A Randomized Controlled Study on the Role of Cognitive Behavioral Therapy in Enhancing Mental Health and Well-Being among Older Adults (International Journal of Food and Nutritional Sciences, 2022)
This randomized controlled study examines the impact of Cognitive Behavioral Therapy (CBT) on reducing depression and improving the quality of life among older adults. A total of 72 individuals aged 65 and above were recruited from [setting] and randomly allocated to either an intervention group receiving CBT or a control group receiving standard care. Key outcomes include changes in depression severity, measured using standardized tools like the Geriatric Depression Scale (GDS), and improvements in quality of life, assessed with the WHOQOL-BREF scale. Evaluations were carried out at three points: before the intervention, after 12 weeks, and at a 6-month follow-up, to assess both immediate and sustained effects. Statistical techniques such as repeated measures paired t-tests and post-hoc analyses will be employed to compare group outcomes and determine the long-term effectiveness of CBT. The study seeks to generate robust evidence supporting the use of CBT as a therapeutic approach for managing depression and enhancing well-being in the elderly population, reinforcing its relevance in geriatric mental health care.